Teaching strategies for environmental education - Stokes, David; Crawshaw, Bruce (Kluwer Academic Publishers, 1986)
It is possible to distinguish four target groups for tertiary environmental education: the Technical Group, the Subject Specialist Group, the Management Group and the Lay Group. Each of these groups requires different sets of skills and abilities. The Technical Group needs to know how to measure environmental parameters. The Subject Specialist Group needs to know about environmental systems. The Management Group needs to have the skills and abilities to resolve complex environmental issues and problems. The Lay Group needs to have attitudes, philosophies and values about the environment. Each of these in turn require different teaching strategies. For the Technical Group, practical experimental teaching methods based on the traditional subject approach appear to be the most suitable. The Subject Specialist Group needs presentational methods based on either an infusion approach or a new subject approach. For the Management Group, a combination of high level disciplinary teaching combined with intensive short skills courses and more extensive 'junctions' or 'environmental encounters', all of which make use of practice methods of teaching, are suggested. For the Lay Group, experiential methods, where the student's attitudes are challenged by experiences in either an in-service situation or through simulation exercises, seem to be most appropriate.